Implementasi kebijakan pengelolaan keuangan desa - Agustinus Ghunu; Cahyo Sasmito; Annisa Purwatiningsih (Publisia: Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this article is to analyze and describe the implementation of village financial management policies (ADD, DD and DBH), as well as the supporting and inhibiting factors in the implementation of village community financial management policies (ADD, DD and DBH) intended to improve welfare and good governance. The implimentation of the management of village finances (ADD DD and DBH) creates  negative phenomena or phenomena that is not on target. The research method  is a qualitative descriptive approach. The results of the  analysis, based on the van Meter and van Horn policy implementation model, indicates that  five of the six variables affect the successful implementation of village financial management policies while one variable, namely the external environment, does not affect the successful implementation of village financial policies. The supporting factors are  the existence of regulations, community participation, internal and external cooperation, while the obstacles are the regulations that often change and the delay in distribution to the RKD. Keywords: implementation, policy, village financial, prosperity, good governance